Comparison of Bubble Continuous Positive Airway Pressure Versus Conventional Ventilation In Neonates with Respiratory Distress Syndrome - Gul Khan, Shaista Imtiaz, Kiren Farooq, Ali Hamza, Shuman Roy, Muhammad Imran, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The use of positive airway pressure in babies with respiratory failure has been associated with significant reductions in respiratory failure, morbidity, and death. The two most popular CPAP techniques are bladder CPAP (B-CPAP) and ventilator-assisted CPAP (V-CPAP). We wanted to see if B-CPAP and V-CPAP have different survival rates and problems. Methods: This retrospective medical trial included 60 preterm babies between 1500- 2500 g who were hospitalized to Mayo Hospital's neonatal critical care unit for breathing difficulties between May 2019 and April 2020. Between May 2019 and April 2020, they were hospitalized for respiratory distress. The patients were allocated to therapy groups at random. To calculate and evaluate survival rates, a survival analysis was done. To compare rates of survival. The t-test for sample data was used to assess the length of supplemental oxygen, hospital stay, and cost of hospital stay. Results: At 24 hours, the predicted survival rates in the B-CPAP and V-CPAP subgroups were 100% and 78%, correspondingly. The comparable results after 48 hours were 100% and 72%. Furthermore, the V-CPAP group's hospitalization expenditures were considerably greater than the B-CPAP groups. Conclusion: Based on our findings, B-CPAP was helpful in treating newborns with breathing difficulties and reduced the hospitalization. In addition to the usual benefits, the lower cost of B-CPAP may be a factor for its widespread use when contrasted to V-CPAP.